Experimental and theoretical evidence of universality in superfluid vortex reconnections - Piotr Z. Stasiak; Yiming Xing; Yousef Alihosseini; Carlo F. Barenghi; Andrew Baggaley; Wei Guo; Luca Galantucci; Giorgio Krstulovic (Proceedings of the National Academy of Sciences, 2025)
The minimum separation between reconnecting vortices in fluids and superfluids obeys a universal scaling law with respect to time. The prereconnection and the postreconnection prefactors of this scaling law are different, a property related to irreversibility and to energy transfer and dissipation mechanisms. In the present work, we determine the temperature dependence of these prefactors in superfluid helium from experiments and a numeric model which fully accounts for the coupled dynamics of the superfluid vortex lines and the thermal normal fluid component. At all temperatures, we observe a pre- and postreconnection asymmetry similar to that observed in other superfluids and in classical viscous fluids, indicating that vortex reconnections display a universal behavior independent of the small-scale regularizing dynamics. We also numerically show that each vortex reconnection event represents a sudden injection of energy in the normal fluid. Finally we argue that in a turbulent flow, these punctuated energy injections can sustain the normal fluid in a perturbed state, provided that the density of superfluid vortices is large enough.